Preparation method and application of Nafion / graphene / PES liquid-Nafion semi-hydrated composite membrane

By hemihydrating on PES to form a breathable liquid Nafion proton exchange membrane and bonding with Nafion/graphene composite membrane, the stability problem of Nafion/graphene composite membrane during electrolysis in liquid water in the prior art is solved, and the effect of long-term electrolysis and hydrogen isotope separation in liquid water is achieved.

CN119633608AActive Publication Date: 2025-03-18XIAMEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411809519.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing Nafion/graphene composite films are prone to bloat and swelling when electrolyzed in liquid water for a long time, resulting in graphene breakdown and cannot effectively perform hydrogen isotope separation in liquid water.

Method used

The liquid Nafion is formed on PES by semihydration method, and is bonded with the Nafion/graphene composite film to form a structurally stable Nafion/graphene/PES-liquid Nafion semihydrate composite film, which is used to perform hydrogen isotope separation in liquid water.

Benefits of technology

The stability of long-term electrolysis in liquid water is achieved, the breakdown of graphene is avoided, and the separation of hydrogen isotopes and the enrichment of heavy water can be effectively carried out.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633608A_ABST
    Figure CN119633608A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of graphene composite membranes, and particularly discloses a preparation method and application of a Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane, and the preparation method comprises the following steps: pasting a copper foil on which graphene grows on a solid Nafion membrane, and enabling one surface, with better graphene growth quality, of the copper foil to be in contact with the solid Nafion membrane; carrying out hot pressing treatment on the device; etching the graphene on the other surface of the copper foil, which is not in contact with the Nafion film, by adopting a dry etching method; removing the copper foil by wet etching; drying at room temperature to obtain a Nafion / graphene composite film; the PES porous membrane is soaked in liquid Nafion, and a PES-liquid Nafion sample is obtained; the sample is placed in a water vapor environment for a semi-hydration reaction, and a PES-liquid Nafion semi-hydration film is obtained; and drying at room temperature, and laminating with the Nafion / graphene composite film to obtain the Nafion / graphene / PES-liquid Nafion semi-hydrated composite film. The prepared semi-hydrated composite membrane can be electrolyzed in liquid water for a long time and kept stable, heavy water can be enriched, and graphene can be well protected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphene composite membrane preparation, and specifically relates to a preparation method and application of a Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane. Background Art

[0002] At present, the conventional preparation method of Nafion / graphene composite membrane is to use hot pressing method, which is to heat press the solid Nafion membrane and the substrate such as copper foil with graphene (Graphene) at about 140℃, apply a certain pressure to directly heat press the solid-solid interface, and then put it into the etching solution to etch away the copper, leaving a clean Nafion / graphene composite membrane. In order to protect the graphene, a layer of solid Nafion membrane is usually hot pressed on the graphene side. This method requires the application of appropriate pressure and has high requirements for the flatness of the substrate. This composite membrane mainly studies the separation of hydrogen isotopes from the perspective of conductivity difference and gas separation. The surface of the solid Nafion membrane is flat, can be softened at high temperature, and the viscosity is enhanced. It can be firmly combined with graphene by applying a certain pressure, so that the graphene can be smoothly transferred down.

[0003] The existing Nafion / graphene composite membrane preparation technology is to composite the solid Nafion membrane with the Nafion / graphene composite membrane at the solid-solid interface. Because a certain amount of pressure must be applied during the process, some uneven areas of the graphene will be squeezed and crushed when combined with the Nafion membrane, thereby damaging the integrity of the graphene film. In addition, since the Nafion membrane is firmly attached to the Nafion / graphene under the hot press, it is easy to bulge when electrolyzed for a long time in a liquid environment, resulting in the breakage of the graphene. In addition, the above-mentioned composite membrane only studies the separation of hydrogen isotopes in terms of conductivity differences and gas separation, and cannot be industrialized. It has not been used for real hydrogen isotope separation in liquid water for a long time. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a preparation method and application of a Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane. Liquid Nafion is semi-hydrated on PES by a semi-hydrated method at a certain temperature to form a breathable proton exchange membrane, and then the membrane is attached to Nafion-graphene to form a structurally stable Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane. The membrane can be used for separation of hydrogen isotopes in liquid water to achieve the purpose of enriching heavy water.

[0005] In order to achieve the above object, the technical solution of the present invention is: a method for preparing a Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane, comprising the following steps:

[0006] (1) attaching a copper foil with graphene grown on it to a solid Nafion membrane, wherein a side of the copper foil with better graphene growth quality is in contact with the solid Nafion membrane;

[0007] (2) subjecting the solid component obtained in step (1) to a hot pressing treatment;

[0008] (3) etching away the graphene on the other side of the copper foil that is not in contact with the Nafion membrane using a dry etching method for the device that has been subjected to the hot pressing treatment in step (2);

[0009] (4) wet-etching the device after the dry etching treatment in step (3) to remove the copper foil therein;

[0010] (5) drying the device after removing the copper foil in step (4) at room temperature to obtain a Nafion / graphene composite membrane;

[0011] (6) soaking a polyethersulfone (PES) porous membrane in liquid Nafion so that the liquid Nafion fills the pores of the PES porous membrane to obtain a PES-liquid Nafion sample;

[0012] (7) placing the PES-liquid Nafion sample obtained in step (6) in a water vapor environment to perform a semi-hydrated reaction to obtain a PES-liquid Nafion semi-hydrated membrane;

[0013] (8) The PES-liquid Nafion semi-hydrated membrane obtained in step (7) is dried at room temperature and then laminated with the Nafion / graphene composite membrane obtained in step (5) to obtain a Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane.

[0014] In a preferred embodiment of the present invention, in step (2), the hot pressing temperature is 130-150° C., the hot pressing pressure is 250-350 kg, and the hot pressing time is 3-7 min.

[0015] In a preferred embodiment of the present invention, the dry etching method in step (3) is oxygen plasma etching.

[0016] In a preferred embodiment of the present invention, the dry etching conditions in step (3) are 70-90 sccmO2, 15-25 sccmAr atmosphere, 40-60 W RF power for 80-120 s.

[0017] In a preferred embodiment of the present invention, the wet etching conditions in step (4) are etching for 2-4 hours in a 0.4-0.6 mol / L ammonium persulfate solution; after etching, it is placed in deionized water for cleaning and soaking to remove the ammonium persulfate on the surface of the device.

[0018] In a preferred embodiment of the present invention, the hemihydration reaction temperature in step (7) is 80-100° C., and the hemihydration reaction time is 5-15 min.

[0019] A Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane prepared by the preparation method of the Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane.

[0020] In a preferred embodiment of the present invention, the above-mentioned layers include PES-liquid Nafion semi-hydrated membrane, graphene, and solid Nafion in order from top to bottom.

[0021] The invention discloses an application of a Nafion / graphene / PES-liquid Nafion semi-hydrate composite membrane for hydrogen isotope separation in liquid water.

[0022] This preparation method is to fuse polymer solutions such as Nafion with porous substrates and then bond them with two-dimensional materials to form a composite membrane; the two-dimensional materials here refer to two-dimensional layered materials such as graphene and its derivatives, transition metal sulfides, transition metal borides, black phosphorus, and topological insulators; the porous substrate refers to all porous media with a porosity between 0 and 1; the polymer solution refers to all high molecular polymer solutions such as carbon chain polymers, heterochain polymers, and elemental organic polymers. After the porous substrate and the solution are fully fused, this stable porous substrate proton exchange membrane / two-dimensional material / solid Nafion composite membrane structure is formed with the two-dimensional material; liquid Nafion uses a semi-hydrated method to form a flat composite membrane with both proton exchange membrane and porous membrane; the two-dimensional material composite membrane can truly perform long-term electrolysis in liquid water to separate hydrogen isotopes.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention forms a breathable proton exchange membrane by semi-hydrating liquid Nafion on PES, and attaches it to the Nafion / graphene composite membrane, which not only protects the graphene but also allows the bubbles generated by electrolysis in liquid water to be breathable, thereby ensuring effective gas permeability and proton conduction during the electrolysis of the graphene side, and does not damage the graphene. The prepared Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane has a stable structure;

[0025] 2. The present invention solves the problem of bulging and swelling of the composite membrane formed by hot pressing of Nafion / graphene membrane and solid Nafion membrane during long-term electrolysis of liquid water for hydrogen isotope separation, thereby damaging graphene;

[0026] 3. The Nafion / graphene / PES-liquid Nafion semi-hydrate composite membrane prepared by the present invention can remain stable during long-term electrolysis in liquid water and can be used for heavy water enrichment. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the structure of the Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane of the present invention;

[0028] Figure 2 This is a SEM photo of the surface of the Nafion / graphene composite membrane of the present invention;

[0029] Figure 3 This is the Raman spectrum test result of the Nafion / graphene composite film of the present invention;

[0030] Figure 4 The air permeability comparison of the solid Nafion, liquid Nafion, PES hemihydrate and PES of the present invention is shown;

[0031] Figure 5 The proton conductivity of solid Nafion, liquid Nafion, PES hemihydrate and PES of the present invention is compared;

[0032] Figure 6 The stability of the composite membrane of the present invention during long-term electrolysis;

[0033] Figure 7 This is a SEM photograph of the surface of the graphene membrane device after electrolysis of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is described in more detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0035] A method for preparing a Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane comprises the following steps:

[0036] (1) A copper foil with graphene grown on the upper and lower surfaces is attached to a solid Nafion membrane, wherein the side of the copper foil with better graphene growth quality is in contact with the solid Nafion membrane;

[0037] (2) subjecting the device obtained in step (1) to a hot pressing treatment;

[0038] (3) etching away the graphene on the other side of the copper foil that is not in contact with the Nafion membrane using a dry etching method for the device that has been subjected to the hot pressing treatment in step (2);

[0039] (4) wet-etching the device after the dry etching treatment in step (3) to remove the copper foil therein;

[0040] (5) drying the device after removing the copper foil in step (4) at room temperature to obtain a Nafion / graphene composite membrane;

[0041] (6) soaking a polyethersulfone (PES) porous membrane in liquid Nafion so that the liquid Nafion fills the pores of the PES porous membrane to obtain a PES-liquid Nafion sample;

[0042] (7) placing the PES-liquid Nafion sample obtained in step (6) in a water vapor environment to perform a semi-hydrated reaction to obtain a PES-liquid Nafion semi-hydrated membrane;

[0043] (8) The PES-liquid Nafion semi-hydrated membrane obtained in step (7) is dried at room temperature and then laminated with the Nafion / graphene composite membrane obtained in step (5) to obtain a Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane.

[0044] In the step (2), the hot pressing temperature is 130-150° C., the hot pressing pressure is 250-350 kg, and the hot pressing time is 3-7 min.

[0045] The dry etching method in step (3) is oxygen plasma etching.

[0046] The dry etching conditions in step (3) are 70-90 sccm O2, 15-25 sccm Ar atmosphere, 40-60 W RF power for 80-120 s.

[0047] The wet etching conditions in step (4) are to etch for 2-4 hours in a 0.4-0.6 mol / L ammonium persulfate solution; after etching, the device is washed and soaked in deionized water to remove the ammonium persulfate on the device surface.

[0048] The semi-hydration reaction temperature in step (7) is 80-100° C., and the semi-hydration reaction time is 5-15 min.

[0049] A Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane prepared by the preparation method of the Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane.

[0050] The method comprises, from top to bottom, a PES-liquid Nafion semi-hydrated membrane, graphene, and solid Nafion.

[0051] The invention discloses an application of a Nafion / graphene / PES-liquid Nafion semi-hydrate composite membrane for hydrogen isotope separation in liquid water.

[0052] Example 1

[0053] A Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane, the structural schematic diagram of which is shown in Figure 1 , prepared by the following preparation method:

[0054] (1) placing a solid Nafion membrane on a PET backplane, and gently attaching a copper foil with graphene grown on both the upper and lower surfaces to the solid Nafion membrane, with the side of the copper foil with graphene grown on it having better quality being in contact with the solid Nafion membrane;

[0055] (2) placing the device obtained in step (1) on a hot press, heating to 140° C., and hot pressing at a pressure of 300 kg for 5 minutes;

[0056] (3) etching the graphene on the other side of the copper foil that is not in contact with the Nafion membrane using an oxygen plasma etching method for the device that has been hot-pressed in step (2); etching conditions are 80 sccm O2, 20 sccmAr atmosphere, 50 W radio frequency power for 100 s;

[0057] (4) The device after the dry etching treatment in step (3) is turned upside down and wet-etched in a 0.5 mol / L ammonium persulfate solution. After 3 hours, the copper foil is completely etched. The device is then placed in deionized water for cleaning twice and soaked for 30 minutes to remove the ammonium persulfate on the surface of the device.

[0058] (5) drying the device after removing the copper foil in step (4) at room temperature to obtain a Nafion / graphene composite membrane;

[0059] (6) soaking a polyethersulfone (PES) porous membrane in liquid Nafion so that the liquid Nafion fills the pores of the PES porous membrane to obtain a PES-liquid Nafion sample;

[0060] (7) placing the PES-liquid Nafion sample obtained in step (6) in a water vapor environment at 90° C. and reacting for 10 minutes to perform a semi-hydrated reaction to obtain a PES-liquid Nafion semi-hydrated membrane;

[0061] (8) The PES-liquid Nafion semi-hydrated membrane obtained in step (7) is dried at room temperature and then laminated with the Nafion / graphene composite membrane obtained in step (5) to finally obtain a Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane.

[0062] The Nafion / graphene composite membrane obtained in step (5) was observed by scanning electron microscopy (SEM), and the results were as follows: Figure 2 As shown, from Figure 2 It can be seen that the transferred graphene is intact without obvious defects, and the graphene coverage is as high as 99%. Raman spectroscopy test of Nafion / graphene composite film, Raman spectroscopy results are as follows Figure 3 As shown in the figure, it can be seen that at 2690cm -1 There is an obvious graphene 2D peak, indicating that graphene is successfully transferred to the Nafion membrane. Figure 4 As shown in the figure, the gas permeability of solid Nafion membrane, liquid Nafion filled into PES semi-hydrated membrane, and single PES membrane was measured under a helium leak detector. The results show that the gas permeability of the liquid Nafion filled into PES semi-hydrated membrane is six orders of magnitude greater than the gas permeability of the solid Nafion membrane. Figure 5 As shown in the figure, the proton conductivity of solid Nafion membrane, liquid Nafion filled into PES semi-hydrated membrane, and single PES membrane were tested. The results showed that the liquid Nafion filled into PES semi-hydrated membrane had a proton conductivity similar to that of solid Nafion membrane. Figure 6 As shown in FIG. 1 , the Nafion / graphene / PES-liquid Nafion semi-hydrate composite membrane is electrolyzed in a PEM electrolyzer, and the composite membrane can work stably for a long time. Figure 7 As shown, the graphene surface of the Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane after electrolysis in a PEM electrolyzer was characterized by SEM. The graphene on the surface of the composite membrane was still on the Nafion membrane after such a long period of electrolysis, indicating that the semi-hydrated membrane filled with liquid Nafion in PES has a protective effect on graphene.

[0063] Liquid Nafion is infiltrated into the porous membrane PES and semi-hydrated to form semi-cross-linked solid Nafion, which is filled in the porous membrane PES to obtain a flat PES-liquid Nafion semi-hydrated composite membrane, which can protect atomic-level graphene by bonding with Nafion / graphene; the PES porous membrane is used as a filling substrate for the Nafion solution and semi-hydrated to form a PES-liquid Nafion semi-hydrated composite membrane, which has a proton conductivity similar to that of the solid Nafion membrane; the PES porous membrane is used as a filling substrate for the Nafion solution and semi-hydrated to form a PES-liquid Nafion semi-hydrated composite membrane, which has a breathability effect equivalent to that of the porous membrane; the prepared composite membrane can be combined with a PEM electrolyzer for electrolysis to achieve true electrolysis in liquid water for more than 600 hours, and it is very stable.

[0064] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane, characterized in that: The following steps are involved: (1) attaching a copper foil with graphene grown on it to a solid Nafion membrane, wherein a side of the copper foil with better graphene growth quality is in contact with the solid Nafion membrane; (2) subjecting the device obtained in step (1) to a hot pressing treatment; (3) etching away the graphene on the other side of the copper foil that is not in contact with the Nafion membrane using a dry etching method for the device that has been subjected to the hot pressing treatment in step (2); (4) wet-etching the device after the dry etching treatment in step (3) to remove the copper foil therein; (5) drying the device after removing the copper foil in step (4) at room temperature to obtain a Nafion / graphene composite membrane; (6) soaking the PES porous membrane in liquid Nafion so that the liquid Nafion fills the pores of the PES porous membrane to obtain a PES-liquid Nafion sample; (7) placing the PES-liquid Nafion sample obtained in step (6) in a water vapor environment to perform a semi-hydrated reaction to obtain a PES-liquid Nafion semi-hydrated membrane; (8) The PES-liquid Nafion semi-hydrated membrane obtained in step (7) is dried at room temperature and then laminated with the Nafion / graphene composite membrane obtained in step (5) to obtain a Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane.

2. The method for preparing the Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane according to claim 1, characterized in that: In the step (2), the hot pressing temperature is 130-150° C., the hot pressing pressure is 250-350 kg, and the hot pressing time is 3-7 min.

3. The method for preparing the Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane according to claim 1, characterized in that: The dry etching method in step (3) is oxygen plasma etching.

4. The method for preparing the Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane according to claim 1, characterized in that: The dry etching conditions in step (3) are 70-90 sccm O2, 15-25 sccm Ar atmosphere, 40-60 W RF power for 80-120 s.

5. The method for preparing the Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane according to claim 1, characterized in that: The wet etching condition in step (4) is etching in a 0.4-0.6 mol / L ammonium persulfate solution for 2-4 hours; After etching, it was washed and soaked in deionized water to remove the ammonium persulfate on the device surface.

6. The method for preparing the Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane according to claim 1, characterized in that: The semi-hydration reaction temperature in step (7) is 80-100° C., and the semi-hydration reaction time is 5-15 min.

7. A Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane prepared by the method for preparing the Nafion / graphene / PES-liquid Nafion semi-hydrated composite membrane as described in any one of claims 1 to 6.

8. A Nafion / graphene / PES-liquid Nafion semi-hydrate composite membrane as claimed in claim 7, characterized in that: From top to bottom, it includes PES-liquid Nafion semi-hydrated membrane, graphene, and solid Nafion.

9. Use of the Nafion / graphene / PES-liquid Nafion semi-hydrate composite membrane as claimed in claim 7 for hydrogen isotope separation in liquid water.

Citation Information

Patent Citations

  • Highly-sulfonated polyether-ether-ketone and graphene oxide copolymer material and proton exchange membrane preparation method thereof

    CN107946619A

  • Graphene complex as well as preparation method and application thereof

    CN117732280A

  • Two-dimensional material / polymer / porous membrane composite membrane and preparation method and application thereof

    CN117942777A

  • Nanofiber membrane-electrode-assembly and method of fabricating same

    US20140038076A1